Peran Accounting & Finance terhadap Incoming Sales di PT. Trans Retail Indonesia - Jonathan Christianto; Arton Briyan Prasetio; Nuno Sutrisno; Beny Beny (Jurnal Abdimas Sosial, Ekonomi, dan Teknologi, 2022)
This internship report is intended to explain the author's activities in the joint internship process at PT. Trans Retail Indonesia through the Independent Campus Certified Internship program organized by the Ministry of Education and Culture. In this report, it will be explained how the author's daily life as part of the accounting and finance internship participants. The things that are explained will include the division of tasks within the Accounting and Finance team, the work assigned by the mentor to the author, and also how the process of carrying out the final project is. The final project takes the theme Flow Incoming sales which contains the flow of incoming money at PT. Trans Retail Indonesia from the store to the head office.